Efficiency evaluation of fiscal input in China's sports industry based on the DEA model - Han, Haotian; Rungsuk, Anong; Sedtheesakolwatchara, Pimsupak (Nimitmai Review Journal, 2024)
The data of Chinese mainland 31 provinces from 2013 to 2022 were selected as samples, and the DEA model and one-way variance analysis were used. The results show that: First of all, the technical efficiency and scale efficiency of the fiscal input in China's leading industry show an upward trend. Secondly, the pure technical efficiency is high in the east and low in the west, lower than the east and higher than the west. The scale efficiency is high in the west and low in the east, lower than the west, higher than the east, and the middle is higher than the east. Third, at present, the technical efficiency of China's fiscal input is relatively low, and it has failed to achieve comprehensive effectiveness. Based on this view:should expand the scale of fiscal investment in the sports industry ,optimize the fiscal input structure of the sports industry and strengthen the supervision and evaluation of the fiscal expenditure of the sports industry. As can be seen from the DEA analysis result, we should further increase the scale of fiscal investment in the sports industry in the western and central regions. Expand the scale of fiscal transfer payments in the western and central sports industry, increase the western and central region of the national fitness, public sports venues, sports parks and community stadium fiscal investment, improve the sports industry guide funds, meet the demand of the masses of the Midwest of sports fitness, strengthen the market main body to participate in the Midwest sports products and services supply enthusiasm. In the central and western regions, the fiscal revenue, the government available fiscal resources and the problem of insufficient investment in the sports industry.